Barriers and enablers in the micronutrient powder supply chain: lessons from a process evaluation of a home fortification programme in Bangladesh - Uddin, Md. Fakhar; Islam, Md. Aminul; Rahman, Mahfuzur; Ahmed, Tahmeed; Sarma, Haribondhu (Frontiers in Nutrition, 2025)
BackgroundBangladesh Rural Advancement Committee (BRAC), a leading non-governmental organization (NGO), implemented a large-scale Home Fortification (HF) with Micronutrient Powder (MNP) programme from 2013 to 2018 aimed to reduce undernutrition and iron deficiency anemia among children aged below 5 years old. An adequate and timely supply of MNP was crucial for successful implementation of the programme, but very few studies have documented implementers’ MNP supply chain experiences. Therefore, this study aimed to explore the barriers and enablers in the MNP supply chain in Bangladesh.MethodsWe conducted this process evaluation in five rural sub-districts and three urban slums from March 2016 to February 2017. We conducted 15 Key Informant Interviews (KIIs) with HF programme personnel, 41 In-depth Interviews (IDIs) with direct HF programme implementers and reviewed relevant documents. We analyzed data using thematic and root-cause analysis approaches.ResultsParticipants reported the barriers in the MNP supply chain included lack of raw materials for MNP production by local manufacturer, political unrest and insufficient transport facilities, a lack of space for MNP buffer stock at BRAC’s central warehouse, and coordination gaps between BRAC’s national and sub-national level staff. Enablers to each of the barriers mentioned include ensuring buffer stock at all levels, raising separate transport requisition for MNP supply, and recruiting dedicated supply chain officers.ConclusionConcurrent course-corrections based on process evaluation findings improved MNP supply chain performance, resulting in higher MNP sales and coverage. The identified barriers and enablers provide useful insights for similar programs, emphasizing the importance of a resilient and well-managed MNP supply chain.